Viruses, genes, and cancer - Hunter, Eric; Bister, Klaus (Springer, 2017)
This volume focuses on virus-host cell interactions, cellular genes acquired or modulated by viruses, the pathological effects of these interactions, and therapeutic interventions. Several chapters specifically address the role of viruses and genes - such as oncogenes, proto-oncogenes, or tumor suppressor genes - in the etiology of human cancer. Oncogenic signaling by PI3 kinase, mTOR, Akt, or the major cancer drivers MYC and RAF, and the role of tumor suppressors like p53, are discussed in detail. The volume also explores the emerging role of noncoding RNAs such as microRNAs in tumorigenesis and cancer therapeutics, and offers new insights into the role of HIV-host interactions relevant to pathogenesis and treatment. Gathering contributions written by leading scientists in their respective fields, the volume offers a valuable resource for researchers and clinicians alike.
Keywords: Viruses.; Viral genetics.; Genes.; Cancer -- Etiology.; elektronické knihy; electronic books